Are Mixed-Gender Committees Less Biased Toward Female and Male Candidates? An Investigation of Competence-, Morality-, and Sociability-Related Terms in Performance Appraisal. (October 2019) - Prati, Francesca; Menegatti, Michela; Moscatelli, Silvia; Kana Kenfack, Corine Stella; Pireddu, Sara; Crocetti, Elisabetta; Mariani, Marco Giovanni; Rubini, Monica
The present research investigated the spontaneous reference to the criteria of competence, morality, and sociability in descriptions made by professional committees evaluating female and male employees' work performance. We examined whether professional committees used different criteria in their performance appraisal of male and female employees and how gender of committee members influences this outcome. The evidence showed that men were primarily evaluated on the basis of their competence, while women were evaluated on the basis of their performance in all the three (evaluative) criteria. Interestingly, using mixed compared with same gender committee members resulted in higher use of competence-related terms rather than sociability and morality ones, regardless of gender of employees. Overall, the evidence reveals that mixed-gender committees provide similar appraisals of male and female employees based on competence, suggesting that they might be an effective way to reduce gender bias in the performance appraisals.